International impact and influence: Three landmark cases from the Canadian law of obligations - Goudkamp, J (LexisNexis, 2018)
This article, written in honour and celebration of Beverley McLachlin’s towering contributions to the common law, focuses on several decisions of the Supreme Court of Canada in the law of obligations. Those decisions, which will be taken in chronological order, are Norberg v. Wynrib, Hall v. Hebert and Bazley v. Curry. Each case has been chosen for discussion for substantially the same reasons. Each has received significant attention, including from judges sitting at the ultimate appellate level, in other major common law jurisdictions, and they are hence excellent vehicles for assessing the influence and importance of McLachlin’s jurisprudence overseas. Each comprises a substantial opinion by McLachlin, which opinions are all exemplars of the lucid, progressive and deliberate style that earned McLachlin recognition as one of the world’s most distinguished jurists. And all of the decisions are closely related to each other in so far as McLachlin’s vision of the law of obligations is concerned with the result that it is profitable to study them collectively.